Nouveaux espaces publics - Bernard Lamizet (Communiquer)
In order to find new ways of thinking about communication, it is important to analyse ruptures and transformations of spaces for exchanges and for dialogues. Public space articulates history, political sciences and communication sciences in a logic of mediation. Thus, public space is defined by what we could call an “indistinct geography”, by a particular link between a real field of law, a symbolic field of discourses and representations, and an imaginary field of projection and fear. In public space, communication is mediated, whereby it is founded upon mediation, i.e. by a particular form of dialectic between a singular dimension of society and the collective field. Last, public space is a sphere for evidences, the manifestation of confrontations between actors and identities.